A new enhancement to avoid video distortion in wireless multihop networks - R.Bulli Babu, Dr; Shahid Afridi, SK; Satya Vasavi, S (International Journal of Engineering and Technology, 2018)
The protocols of typical routing algorithms which are designed for the wireless networks long back are specifically application oriented. Taking consideration at present, with the increase in the usage of the wireless networks the problem we are facing is video traffic. The very important thing is to maintain a good quality of video. At present users are opting videos in high quality that are to be delivered smoothly into their devices. The nature of video is changed due to 1) Because of the compression distortion occurs at the source. 2) With both interference and the errors induced on wireless channels distortion occurs. Hence, in this paper we work for the reduction of the distortion that occurs in video traffic. In order to overcome this problem we opted a wireless network in which the flow of application contains video traffic. For the clients the reduction of the distortion is very difficult. We cannot minimize the video distortions by using the link quality based routing measures. To understand this we construct an analytical framework first, then on the video distortions for accessing the impact. By using an analytical framework we design a routing measure for the reduction of distortion. With our experiment results we evaluate that our protocol is best for the reduction of video distortion and also for the reduction of the experience of user de-gradations.
Keywords: Analytical Framework; Minimization of Distortion; Routing Protocol Design; Video Distortion.